The use of fuzzy logic to determine the concentration of betel leaf essential oil and its potency as a juice preservative. (1st February 2018) - Basak, Suradeep
Highlights: Fuzzy logic analysis was used to determine acceptable dose of BLEO in RAJ. Effect of the BLEO dose in unpasteurized RAJ during storage at 4 °C was studied. Application of BLEO in microemulsified form has potential as RAJ preservative. Abstract: The present study was attempted to determine organoleptically acceptable concentration of betel leaf essential oil (BLEO) in raw apple juice using fuzzy logic approach, and to evaluate the efficacy of the acceptable concentration in the juice under refrigerated storage. The presence of BLEO components in treated juice was confirmed by FTIR spectroscopy. Based on similarity values, the acceptable concentration in the juice was found to be 0.19 µl/ml of BLEO. Total antioxidant capacity of untreated juice was found to be 16% less than treated juice at the end of storage. The treated juice exceeded total aerobic plate count of 2 log10 (cfu/ml) on 15th day of storage. Based on safe limits of microbial load, the shelf life of treated juice was extended by 6 days as compared to untreated juice under refrigerated storage. BLEO contributes to green consumerism and its application as food preservative will add value to the product.